APPLICATION OF DELPHI METHOD IN PRIORITIZATION OF CRITICAL SUCCESS FACTORS OF TQM FOR THE INDONESIAâS OIL AND GAS INDUSTRY - Ciptono, Wakhid Slamet (Journal of Indonesian Economy and Business, 2005)
The study describes the use of the policy Delphi method in building consensus for theprioritization of critical success factors of TQM (CSFs of TQM). The use of multi attributedecision analysis for supporting the qualitative data analysis (multifactor evaluationprocess, analytic hierarchy process, and NVivo) has been considered the foremosttechnique for examining the manages needs and the weightings of preferences from thepanel of managers for each CSFs of TQM in the most objective way available. Two roundof Delphi surveys were conducted. A significant consensus on the weighted evaluation ofthe six CSFs of TQM and the consistency ratio were obtained from twenty managers. Theresults vividly reveal that the Delphi method is a powerful and appropriate technique forderiving objective opinions in a rather subjective area such as the multi-attribute model for the prioritization of the CSFs of TQM.The results of qualitative data analysis (using MFEP) indicate that training to improveproducts/services provides the first priority (the weighted evaluation 0.184; 0.224; and0.169 for top level managers, middle kevel managers, and low level managers); followed by Quality Improvement, Top Management Commitment, Supplier Involvement, Cross-Functional Relationships among SBUs, and Supervisory Leadership.In addition, the qualitative data analysis (using AHP) also provides a set of sufficientlyconsistent CSFs of TQM was obtain after the second round of Delphi questionnaire. Theresult of consistency ratio (CR) shows that the managers had highly satisfactory inassessing the prioritization of CSFs of TQM (CR = 0.0456). Therefore, these CSFs of TQMwere supported the results from the quantitative data analysis.Oil and gas managers in Indonesia can use these qualitative data results in concertwith other critical quality management practices to help them in there word-class company initiatives. The researcher recommended the use of Delphi method as an objective and rigorous determining consensus. Researchers can also use this method to combine qualitative and quantitative research approaches into mixed methodology or triangulation.Keywords: Delphi Method, Qualitative Data Analysis, Critical Success Factors of TQM,Multifactor Evaluation Process, Analytic Hierarchy Process, and NVivo.